Un entre-deux entre laïcité et religions pour penser la spiritualité en éducation - Muriel Briançon; Florent Pasquier; Jean-Marc Lamarre; Hélène Hagège
This collaborative and exploratory effort intends to give an overview of spirituality in education and training by posing the terms of a debate : to what extent spirituality can and/or should it be a reference for secular education ? In fact, spirituality, the collateral victim of the principle of secularism, was seen - at the same time as religions - rejected by the Public School. However, this controversial notion is still inadequately conceptualized in education. We will show that spirituality, closely delimited by its secular and religious borders, can be conceived precisely as a margin, an in-between, that different theoretical models (philosophical, psychological, transdisciplinary or comparative) are seeking to understand now directly in education and training.